HUBUNGAN KETENAGAKERJAAN DAN PERUBAHAN STRUKTUR EKONOMI TERHADAP KESEJAHTERAAN MASYARAKAT DI KOTA LANGSA - Lisa, Lisa Dahlia; Muhamamd Salman; Ahmad Ridha; Suri Amilia; Reza Putra (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study aims to analyze and determine the relationship between employment and changes in the economic structure of the people's welfare in Langsa City. Welfare is an order of life and social, material and spiritual livelihood that is filled with a sense of safety, decency and inner and outer peace that allows every citizen to carry out efforts to fulfill the best possible physical, spiritual and social needs for himself, his household and Public. Workers are residents who have or are currently working, who are looking for work, and who carry out other activities such as going to school and taking care of the household. In practical terms, according to him, the notion of labor and non-labor is only differentiated by the age limit. The results of this study indicate that employment affects welfare through changes in economic structure. This explains that with an increase in the workforce of working age people in Langsa City who are actively involved, it will be followed by changes in the economic structure in the non-agricultural sector. So that with changes in the economic structure it will have a positive and significant effect on the welfare of the people in Langsa City. This explains that changes in the economic structure that occur in the increase in the distribution of the non-agricultural sector positively increase the welfare of the community.